Sensing nature in the city: The role of sight and sound in restorative tropical urban green spaces - Juliana Ju Yun Hoo; Shumetha Sidhu; Kok Wei Tan (PLoS ONE, 2026)
Rapid urbanization has increased disconnection from nature, especially in cities. While research on restorative environments has largely focused on non-tropical regions, little is known about the restorative potential of tropical urban green spaces (UGSs). This study assessed the perceived restorativeness of tropical UGSs in Malaysia using 120 environmental stimuli from nature, urban, and mixed urban-nature settings. 87 participants were randomly assigned to one of the three modalities: audio-only, visual-only, or bimodal. Each participant rated a subset of 30 stimuli on perceived restorativeness. Results showed that nature and mixed urban-nature scenes were in general rated as more restorative than urban scenes. An interaction effect indicated that, in the visual-only modality, mixed urban-nature scenes were perceived as more restorative than nature scenes, while no significant differences were observed in the audio-only and bimodal modalities. Moreover, perceived restorativeness for nature scenes was comparable across bimodal, visual-only, and audio-only presentations. These findings suggest that small pockets of urban nature (e.g., tree-lined streets, rooftop gardens) can offer greater psychological restoration than wild, untamed forests. In addition, high-quality nature sounds (e.g., birdsong, flowing water) can provide restorative benefits comparable to visual exposure when access to green views is limited. Such insights can inform urban planning strategies to design more restorative and liveable cities.